The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0042098010368575
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation, Poverty and Sexual Behaviour

Abstract: The question of how urbanisation and poverty are linked in sub-Saharan Africa is an increasingly pressing one. The urban character of the HIV epidemic in sub-Saharan Africa exacerbates concern about the urbanisation - poverty relationship. Recent empirical work has linked urban poverty, and particularly slum residence, to risky sexual behaviour in Kenya's capital city, Nairobi. This paper explores the generalisability of these assertions about the relationship between urban poverty and sexual behaviour using D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…34,37,79,117,139,140 Poverty compromises overall health and access to health care, including testing and treatment for STIs and HIV. It not only restricts access to condoms, but also influences sexual practices and partnerships, creating barriers to condom use.…”
Section: Povertymentioning
confidence: 99%
“…34,37,79,117,139,140 Poverty compromises overall health and access to health care, including testing and treatment for STIs and HIV. It not only restricts access to condoms, but also influences sexual practices and partnerships, creating barriers to condom use.…”
Section: Povertymentioning
confidence: 99%
“…Zulu, Dodoo, and Chika-Ezeh (2002) found out that slum residents start sexual intercourse earlier and are more likely to be involved with multiple sexual partners than non-slum residents in Nairobi, Kenya. Similarly, Greif, Dodoo, and Jayaraman (2010) found that risky sexual practices such as the early onset of sex, low use of condoms and involvement with multiple sexual partners are more common among slum residents than non-slum residents in several parts of sub-Saharan Africa. Dodoo, Zulu, and Ezeh (2007) further showed that poverty is associated more with risky sexual outcomes among the urban poor than the rural poor in Kenya.…”
Section: Research Problemmentioning
confidence: 97%
“…Some of these risk behaviours have been explained among various groups in different studies (Mpofu et al 2006;Greif et al 2011;Lundberg et al 2012).…”
Section: Risk Behavioursmentioning
confidence: 99%